Submental Area Treatment with ATX-101: Relationship of Mechanism of Action, Tissue Response, and Efficacy. Issue 4 (27th April 2022) - Humphrey, Shannon; Munavalli, Girish S.; Yoelin, Steven G.; Friedmann, Daniel P.; Kavali, Carmen M.; Sangha, Sara
Abstract : Background: ATX-101 is an injectable, synthetically derived formulation of deoxycholic acid used for submental fat reduction. Methods: A narrative review of references relevant to the mechanism of action of ATX-101 and its relationship to efficacy and inflammatory adverse events was conducted. Results: When injected into subcutaneous fat, deoxycholic acid physically disrupts adipocyte cell membranes, leading to local adipocytolysis, cell death, and a mild, local inflammatory reaction consisting of macrophage infiltration and fibroblast recruitment. At Day 28 postinjection, inflammation largely resolves, and key histologic features include fibrotic septal thickening, neovascularization, and atrophy of fat lobules. Based on the mechanism of action of ATX-101 and the demonstrated inflammatory response, localized inflammation and swelling are expected following treatment. Indeed, postinjection swelling and other local injection-site events, including pain, erythema, and bruising, are common during and after treatment. Because of inflammatory sequelae following injection, reduction in submental fat is gradual and may require months before the full response is apparent. Patients may also require multiple treatment sessions to achieve their treatment goals. Repeated treatments may result in less pain and swelling over time owing to a combination of factors, including less target tissue allowing for lower doses/injection volumes, persistent numbness, and greater tissue integrity from thickened fibrous septa. Conclusions: Physicians can manage expectations by counseling patients that, based on the mechanism of action of ATX-101 and data from pivotal clinical trials, ATX-101 treatment results in localized inflammation/swelling and gradual submental fat reduction. Patient education about common local adverse events is critical.